Training devices in psychology teaching (Praxis Educativa, 2012)
This work is the result of a process of reflection concerning our own teaching practice. From that perspective we encourage the construction of devices that would allow grasping the significance of the interaction between teachers (teaching subject), trainee (training subject) and knowledge (specific contents of a subject, pedagogical, institutional). The Chair as a space of development fosters the analysis and consideration of our own practice, steps that will bring about a set of questions about the singularity of the teaching and learning processes. The process of reflection and re-signification shapes a personal teaching style, which requires that the teacher trainer and the trainee acknowledge the value of inter-subjectivity as a constitutive element of the professional role.
Keywords: teaching practice; training; inter-subjectivity